THE RADIO WAVES PROPAGATION CHARACTERISTICS IN THE GLIDESLOPE AXES OF THE GROUND CONTROLLED APPROACH SYSTEMS IN THE ARCTIC REGIONS - G. S. Nakhmanson; D. V. Buchnev; A. V. Bunin (Научный вестник МГТУ ГА)
Information about the location of the aircraft, with a decrease along a predetermined path, the carriages, the floor-fer with the use of radio landing systems. On the trajectory of radio wave propagation in the channels of the radio glide path landing systems affected by the change of refractive index in the atmosphere depending on altitude. Known methods of calculation of the angular deviations of trajectories of propagation of radiation from the nominal glide path line. Currently in the Arctic regions, a network of airfields, so it is necessary to have data of possible distortions of the trajectories of propagation in the channels of the glide path radio systems on such airfields. The article analyzes the angular deviation of the trajectories of propagation in the channels of the radio glide path landing system of aircrafts on the basis of temperature-wind sounding of the atmosphere. Calculated parameters of the probability density functions of these deviations at different distances from the runway for three Arctic regions of Russia. The article shows that the magnitude of the confidence intervals of deviations of trajectories at the required value of confidence probability is 2-4 times the size of the area tolerance. Contained in the article the results clearly indicate the necessity of considering the influence of the atmosphere on the trajectory of radio wave propagation in channels of radio glide path landing system in flight operations to improve safety of aircraft landing in the Arctic regions.